Energy balance - Halula, Wes; Halula, Jenica; Harnist, Billy; Learning ZoneXpress (Firm).; ChooseMyPlate.gov ([Owatonna, MN] : Learning Zonexpress, 2012)
This 20 minute DVD features MyPlate dietary guidelines. In it a dietitian and a personal trainer help the viewer discover the best food choices, short term and long term benefits of physical activity, tips to be active each day, how to overcome common excuses and how to continue being active into adulthood.
Title from container.
'Featuring the USDA's MyPlate Dietary Guidelines'--from container.
writer, Jenica Halula.
Featuring Melissa Halas-Liang and Dwayne Arthur Jones.
Host : Davina Joy.
Grades 6-adult.
Keywords: Nutrition; Health behavior; Food